ANALISIS FAKTOR-FAKTOR LINGKUNGAN KERJA FISIK DAN LINGKUNGAN KERJA NON FISIK TERHADAP KINERJA KARYAWAN PADA PT DAMAI SENTOSA CIMANGGIS - Bintang Aditya Darmawan; Leonard Siahaan (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aims to analyze the influence of the Physical Work Environment and Non-Physical Work Environment on Employee Performance at PT Damai Sentosa Cimanggis. The main problem identified is the inadequate quality of the work environment and the inaccuracy of information provided by the company, which affects employee performance. This study employs three variables, namely Physical Work Environment, Non-Physical Work Environment, and Employee Performance. The population of this study consists of employees of PT Damai Sentosa Cimanggis, with a sample of 50 respondents. The research method used is quantitative, and data were collected through questionnaires distributed to the employees of PT Damai Sentosa Cimanggis. The data were tested for validity and reliability, while the analytical method used was multiple linear regression analysis with data processing conducted using IBM SPSS version 27. The results of the study indicate that the Physical Work Environment has a positive and significant effect on Employee Performance, with a t-value of 2.362 greater than the t-table value of 2.011 and a significance value of 0.022 lower than 0.05. The Non-Physical Work Environment also has a positive and significant effect on Employee Performance, with a t-value of 3.156 greater than the t-table value of 2.011 and a significance value of 0.003 lower than 0.05. Furthermore, the Physical Work Environment and Non-Physical Work Environment simultaneously have a positive and significant effect on Employee Performance, with an F-value of 36.261 greater than the F-table value of 3.20 and a significance value of 0.001 lower than 0.05. Therefore, it can be concluded that both the Physical Work Environment and Non-Physical Work Environment significantly influence Employee Performance at PT Damai Sentosa Cimanggis.